Safety and efficacy of apixaban in patients with glomerulonephritis and nephrotic syndrome: a prospective longitudinal cohort study - I. S. Mykhaloiko; R. I. Yatsyshyn; I. O. Dudar; O. I. Hotsaniuk; H. M. Kuryliv (Сучасні медичні технології)
Aim. Assessment of the efficacy and safety of apixaban in preventing thromboembolic complications in patients with nephrotic syndrome caused by primary glomerulonephritis.